2001
DOI: 10.1073/pnas.061013598
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific mutations accumulate with aging in critical human mtDNA control sites for replication

Abstract: The recently discovered aging-dependent large accumulation of point mutations in the human fibroblast mtDNA control region raised the question of their occurrence in postmitotic tissues. In the present work, analysis of biopsied or autopsied human skeletal muscle revealed the absence or only minimal presence of those mutations. By contrast, surprisingly, most of 26 individuals 53 to 92 years old, without a known history of neuromuscular disease, exhibited at mtDNA replication control sites in muscle an accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
6
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 19 publications
11
150
6
1
Order By: Relevance
“…Similar cases had already been found in other tissues [3,4] and for other somatic mutations [23]. In the present case, the A189G tissue variability (that is, the difference in both appearance age and heteroplasmy rate variability), could be explained by a difference in the metabolism of muscle and bone [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar cases had already been found in other tissues [3,4] and for other somatic mutations [23]. In the present case, the A189G tissue variability (that is, the difference in both appearance age and heteroplasmy rate variability), could be explained by a difference in the metabolism of muscle and bone [24].…”
Section: Discussionsupporting
confidence: 89%
“…This oxidative stress increase could thus be at the origin of all cellular molecule damage and in particular, could induce the accumulation of lesions on mitochondrial DNA (mtDNA). These lesions were found in numerous tissues with high metabolism, especially in post-mitotic tissues [3,4,5]. They took several forms -mostly insertions, deletions and heteroplasmic point mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in humans and rodents, DNA mutations are also highly prominent in the muscle of aged individuals (Wang et al 2001;Szczesny, Tann & Mitra 2010). Furthermore, the accumulation of dysfunctional mitochondrial proteins during aging is higher, and the levels of the antioxidant enzymes are lower in mouse skeletal muscle compared to other tissues (Szczesny, Tann & Mitra 2010).…”
Section: Skeletal Musclementioning
confidence: 99%
“…The point mutations, A189G and T408A, were identified in skeletal muscle. The fibroblastspecific T414G was absent in muscle and heart in several studies (Calloway et al ., 2000;Wang et al ., 2001;Nekhaeva et al ., 2002) yet another study found T414G in muscle but not in brain (Murdock et al ., 2000). A more recent study has linked reduced COX activity to an increasing burden of multiple mtDNA point mutations, rather than a single specific point mutation, present in the genes coding for COX (Lin et al ., 2002).…”
Section: High Levels Of Mtdna Mutations Cause Diseasementioning
confidence: 99%